Profit Sharing System between Owners and Managers of Oil Palm Plantations at Sungai Kayu Aro Village - Saputra, Ahmad Edi (CV. Zabags Qu Publish, 2024)
This study aims to determine the profit-sharing system, obstacles and solutions for profit-sharing between oil palm plantation owners and managers in the Sharia Economic Perspective in Sungai Kayu Aro Village, Senyerang District, West Tanjung Jabung Regency. The approach method uses qualitative analysis of primary data. The sample consists of plantation owners, plantation managers, and community leaders and government figures. Data collection methods use observation, interviews and documentation. Data analysis tools; data reduction, data display, and conclusions. Based on the results of observations and interviews in the field, it was found that the obligations between owners and managers include (a) owner obligations; provision of land, provision of grass, provision of seeds, and provision of fertilizer (b) manager obligations; provision of land processing tools, provision of maintenance tools, and provision of fertilization tools. The constraints of managers are only having limited capital and having to bear damage to equipment. The profit-sharing system between owners and managers includes; (a) first, 50% owner and 50% manager, with the note that the capital, equipment and damage are borne by the manager, (b) second, 65% for the owner and 35% for the manager, with the note that the owner bears the costs, while the manager bears all costs of damage to the equipment.